Braving the Elements: Ambivalence as Opportunities for Change in Individual Psychotherapy With Men Using Intimate Partner Violence - Todd-Kvam, Mari; Lømo, Bente; Tjersland, Odd Arne (Frontiers in Psychology, 2019)
This study examines client utterances that can be understood as ambivalent in violence-focused therapy. The purpose is to enrich our scientific understanding of client contributions to therapy when they appear ambivalent to the therapeutic project and develop clinically relevant perspectives that enable us to help this and other client groups. Using constructivist grounded theory analysis of five completed therapies, we describe three categories of client ambivalence present throughout all five therapies: I am bad, but I am not that bad; I have tried and tried in vain; and I know it is wrong, but I have to, I have no choice. The categories are described and understood from a clinical perspective. They are developed on the basis of an interpretation of what seems to be at stake for the client in the here-and-now of therapy. Clinical implications are discussed.